Pembaharuan Pengelolaan Pesantren Tradisional: Studi Kasus di Pesantren Al Hikmah 2 Benda Sirampog Brebes - Waidi Waidi; Didin Saefudin; E. Mujahidin (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This research is motivated by representatives of change in education in traditional Islamic boarding schools which are academic considerations of the tradition and mordenization of the pesantren education system which the leaders of Islamic education have raised more goals for pesantren. Therefore this study was formulated to describe the Renewal of Management of Traditional Islamic Boarding Schools in Al-Hikmah Islamic Boarding School in the Object of Sirampog Brebes, Central Java. The method used in this study is a qualitative method with descriptive research. This research succeeded in completing the renewal of the pesantren tradsional Al-Hikmah Education. The Sirampog Brebes object functioned integrally in responding to changes based on the pesantren culture which contained First, the purpose of the pesantren education that could not be used for tafaqquh fi al-din would also be used for this information, social and politics and technology. Second, the aspect of pesantren education programs is adaptive while maintaining the kitab kuning (classic book) that is adapted to current knowledge and technology. The third Islamic boarding school, the innovative aspect, using the sorogan, bandongan and wetonan models that are characteristic of pesantren, but there are efforts to improve the pattern of pesantren in the supported pesantren, and teaching materials, values ​​and ways of life in pesantren, because has advantages.